Bombast and broadsides : the lives of George Johnstone - Fabel, Robin F. A., 1934- (University of Alabama Press, 1987)
George Johnstone has never received the scholarly attention he fully merits. Historians have assessed him, usually briefly, as governor of West Florida, or as naval commander, or as a member of parliament. Nevertheless, none has considered his important role in East India Company politics, nor, until Bombast and Broadsides, has one synthesized the various roles in which Johnstone was entrusted with high responsibilities. Through research in Cardiff, Edinburgh, Kew, London, Philadelphia, and Washington in largely unpublished manuscripts, together with the use of secondary sources,